Influencer-Based Marketing Strategies for Culinary Businesses on Instagram - Rafael Tarigan; Rodhita Hutabarat; Sabella Silalahi (CV. Visionary Raya Sakti, 2026)
Purpose: This study aims to examine the reasons why small-scale and home-based culinary business owners increasingly adopt Instagram influencer marketing despite its uncertain outcomes. It also seeks to evaluate the extent to which collaboration with influencers affects customers’ purchase intentions and contributes to business growth. Design/methodology/approach: A quantitative approach was employed through an online questionnaire distributed to 22 owners of various culinary businesses, most of which operate on a small or home-based scale. The collected data were analyzed to identify patterns in Instagram usage, influencer collaboration practices, and consumer responses to promotional activities. Findings: The findings reveal that 77.3% of respondents manage home-based culinary businesses and rely on Instagram as their primary marketing channel. Influencer marketing significantly increases consumer interest, particularly when integrated with Instagram’s visual features such as Stories, Reels, and feed posts. These features enhance brand exposure and foster positive consumer attitudes. However, small businesses face notable challenges, including high collaboration costs and difficulties in measuring the tangible impact of influencer campaigns. Research implications: This study highlights the strategic importance of Instagram influencer marketing for small culinary enterprises in improving brand awareness, customer engagement, and sales performance. However, sustainable outcomes require integration with original content creation, direct customer interaction, and participatory promotional strategies. The findings contribute to the understanding of digital marketing adoption among micro and home-based food businesses and provide practical insights for optimizing influencer collaborations.